Growth of Graphene and Combination with Dielectric Materials for New Electronic Devices - Marquez Velasco, Jose (Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2016)
Graphene is a two-dimensional material with very promising prospects for applications on electronic devices of new generation. In this work we have optimized the process to grow single layer graphene on copper substrates by chemical vapor deposition. Large areas of single layer graphene with low defect densities were certified by Raman spectroscopy. Although Raman spectroscopy is widely used to study the number of graphene layers when the layers are AB stacked, the method has limitations when it deals with other stacking orders. We demonstrated that ARPES measurements can be used to determine the number of layers of non-AΒ stacked graphene grown on single crystal Cu(111). Thus, we found that we had three rotated graphene layers with a relative angle of ~4° between them. Another approximation to the single layer graphene was tried. From a sample with AB stacked multi-layer graphene, the number of layers were reduced by etching the sample at hydrogen atmosphere while using mild temperatures during the annealing. However, we did not achieve our principal goal to reduce the sample to single layer graphene. Instead we managed to reduce the sample to AB-stacked few-layers graphene, which is also interesting since it is not easy to grow large areas of AB stacked few-layers graphene by chemical vapor deposition. It is worth mentioning that the process did not introduce noticeable defects on the lattice. The whole process was certified by Raman spectroscopy and XPS. We achieved to encapsulate graphene in MIS device gates. The transfer method was optimized, as well as the Al2O3 deposition, to avoid graphene defects. C-V curves were measured on capacitors with and without graphene embed in order to analyze the effect of graphene in the structure. The results show a large enhancement of the total capacitance of up to 35% in the accumulation, above the geometrical capacitance. This was related to the negative quantum capacitance contribution of graphene by a theoretical model of the device. Finally, the stability of graphene on different two-dimensional substrates such as hAlN/Ag111, h-BN/Ni111, HfSe2/Ni111 and MoSe2/TaSe2 was studied by density functional theory. Also, the study of the electronic properties of the structures mentioned before shows that dielectrics with a larger band gap (h-AlN, h-BN and MoSe2) do not affect the electronic properties of graphene while the dielectric with smaller band gap (HfSe2) clearly affect the graphene LDOS. From the point of view of metals, it is shown that Ag(111) alters more significantly the LDOS of graphene than Ni(111) or TaSe2. Additionally, DFT method was used to analyze ARPES measurements of different twodimensional transition metal dichalcogenides such as TaSe2, ZrSe2 and HfSe2.